Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research, in press)

Die Kriterien und Zusammensetzung der EU-Blacklist als Grundlage des Steueroasen-Abwehrgesetzes – Eine kritische Würdigung - Schön, Lena; Graßl, Benjamin; Giese, Henning (Steuer und Wirtschaft)

Persis - Breuer, Saskia Rebecca (Encyclopedia of the Bible and its Reception (EBR))

Effect of DNA Origami Nanostructures on Bacterial Growth - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
DNA origami nanostructures are a powerful tool in biomedicine and can be used to combat drug‐resistant bacterial infections. However, the effect of unmodified DNA origami nanostructures on bacteria is yet to be elucidated. With the aim to obtain a better understanding of this phenomenon, the effect of three DNA origami shapes, i.e., DNA origami triangles, six‐helix bundles (6HBs), and 24‐helix bundles (24HBs), on the growth of Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis is investigated. These results reveal that while triangles and 24HBs can be used as a source of nutrients by E. coli and thereby promote population growth, their effect is much smaller than that of genomic single‐ and double‐stranded DNA. However, no effect on E. coli population growth is observed for the 6HBs. On the other hand, B. subtilis does not show any significant changes in population growth when cultured with the different DNA origami shapes or genomic DNA. The detailed effect of DNA origami nanostructures on bacterial growth thus depends on the competence signals and uptake mechanism of each bacterial species, as well as the DNA origami shape. This should be considered in the development of antimicrobial DNA origami nanostructures.
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Photochemical Reaction Enabling the Engineering of Photonic Spin−Orbit Coupling in Organic-Crystal Optical Microcavities - Liang, Qian; Ma, Xuekai; Gu, Chunling; Ren, Jiahuan; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (Journal of the American Chemical Society (JACS))

Special Section/Schwerpunkt: Poetologien mehrdeutigen Erinnerns. Historisierungsstrategien in der deutschsprachigen Gegenwartsliteratur (andererseits. Yearbook of Transatlantic German Studies 11/12 (2022/23))

Poetologien mehrdeutigen Erinnerns in der deutschsprachigen Gegenwartsliteratur. - Eke, Norbert (andererseits. Yearbook of Transatlantic German Studies 11/12 (2022/23))

Maghemite nanoparticles synthesis via spray flame synthesis and particle characterization by hole in a tube sampling and scanning mobility particle sizing (HIAT-SMPS) (Applications in Energy and Combustion Science)
In order to standardize spray flame synthesis (SFS) studies, intensive work has been done in recent years on the design of burner types. Thus, in 2019, the so-called SpraySyn1 burner was introduced (SS1), which was subsequently characterized in numerical and experimental studies. Based on this research, a modification of the nozzle design was proposed, which has now been considered in the successor model, SpraySyn2 (SS2). As little is known about the effect of the nozzle adaptation on the particle formation, we operated both burners under identical operating conditions to produce maghemite. The final powder comparison showed that SS2 yielded considerable higher specific surface areas (associated with smaller primary particle sizes), lower polydispersity, and higher phase purity. To obtain further information on the size distributions of aggregates and agglomerates generated by SS2, aerosol samples were extracted by hole in a tube (HIAT) sampling and characterized by scanning mobility particle sizing (SMPS). Samples were extracted along the centerline at different heights above the burner (HAB) above the visible flame tip (>7 cm), and quenching experiments were performed to extract the aerosol samples at different dilution rates. Thereby, it was demonstrated that performing detailed quenching experiments is crucial for obtaining representative HIAT-SMPS data. In particular, agglomerates/aggregate sizes were overestimated by up to ~70 % if samples were not sufficiently diluted. If sufficient dilution was applied, distribution widths and mean particle mobility diameters were determined with high accuracy (sample standard derivation <5 %). Our data suggested the evolution of primary particle sizes was mostly completed <7 cm HAB and it was shown aggregates/agglomerates present above the visible flame were compact in structure (non- fractal). The mean diameter of the particle ensemble grew along the centerline from 6.9 nm (7 cm) to 11.4 nm (15 cm), while distribution widths grew from 1.42 to 1.52.
Keywords: Flame Spray Pyrolysis; SpraySyn2; Spray flame synthesis; Maghemite nanoparticles; Gas to particle-conversion; Hole in a tube sampling

„Es nimmt der Raum gastfreundlich auf die Menge“. Theodor Hells Prolog zur Eröffnung des Dresdner Hoftheaters (1841) - Eke, Norbert Otto (Die Kunst der Theatereröffnung. Ästhetik und Sozialgeschichte von Bühnenprologen)

„Wenn die Heilige Zeit da ist, werde ich […] weggehen“. Heilige Zeit in Claudia Llosas Madeinusa - Eke, Norbert Otto ((Un)verfügbar – Kulturen des Heiligen)

Das Heilige – Versuch einer Definition - Eke, Norbert Otto ((Un)verfügbar – Kulturen des Heiligen)

Artaud ± Brecht Peter Weiss’ Theater-Revolution (Marat/Sade) - Eke, Norbert Otto (Studia theodisca 31)

Heinrich von Kleist. Artistic and Aesthetik Legacies - High , Jeffrey L.; Collenberg-González, Carrie (Amsterdamer Beiträge zur neueren Germanistik)

Equivalent-circuit model that quantitatively describes domain-wall conductivity in ferroelectric lithium - Zahn, Manuel; Beyreuther, Elke; Kiseleva, Iuliia; Lotfy, Ahmed Samir; McCluskey, Conor J.; Maguire, Jesi R.; Suna, Ahmet; Rüsing, Michael; Gregg, J. Marty; Eng, Lukas M. (Physical Review Applied)
Ferroelectric domain wall (DW) conductivity (DWC) can be attributed to two separate mechanisms: (a) the injection/ejection of charge carriers across the Schottky barrier formed at the (metal-)electrode-DW junction and (b) the transport of those charge carriers along the DW. Current-voltage (I-U) characteristics, recorded at variable temperatures from LiNbO3 (LNO) DWs, are clearly able to differentiate between these two contributions. Practically, they allow us to directly quantify the physical parameters relevant to the two mechanisms (a) and (b) mentioned above. These are, for example, the resistance of the DW, the saturation current, the ideality factor, and the Schottky barrier height of the electrode-DW junction. Furthermore, the activation energies needed to initiate the thermally activated electronic transport along the DWs can be extracted. In addition, we show that electronic transport along LNO DWs can be elegantly viewed and interpreted in an adapted semiconductor picture based on a double-diode, double-resistor equivalent-circuit model, the R2D2 model. Finally, our R2D2 model was checked for its universality by successfully fitting the I-U curves of not only z-cut LNO bulk DWs, but equally of z-cut thin-film LNO DWs, and of x-cut thin-film DWs as reported in literature.
Keywords: General Physics and Astronomy

Extended Dynamic Mode Decomposition: Sharp bounds on the sample efficiency - Philipp, Friedrich M.; Schaller, Manuel; Boshoff, Septimus; Peitz, Sebastian; Nüske, Feliks; Worthmann, Karl (arXiv:2402.02494)
We rigorously derive novel and sharp finite-data error bounds for highly sample-efficient Extended Dynamic Mode Decomposition (EDMD) for both i.i.d. and ergodic sampling. In particular, we show all results in a very general setting removing most of the typically imposed assumptions such that, among others, discrete- and continuous-time stochastic processes as well as nonlinear partial differential equations are contained in the considered system class. Besides showing an exponential rate for i.i.d. sampling, we prove, to the best of our knowledge, the first superlinear convergence rates for ergodic sampling of deterministic systems. We verify sharpness of the derived error bounds by conducting numerical simulations for highly-complex applications from molecular dynamics and chaotic flame propagation.

Qualitätsoffensive Ganztag - Praktische Methoden für den Weg zur guten Ganztagsbildung - Seitz, Simone; Hamacher, Catalina; Schieffer, Leonie; Bunte, Charline

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

A note on the convergence of deterministic gradient sampling in nonsmooth optimization - Gebken, Bennet (Computational Optimization and Applications)
Abstract Approximation of subdifferentials is one of the main tasks when computing descent directions for nonsmooth optimization problems. In this article, we propose a bisection method for weakly lower semismooth functions which is able to compute new subgradients that improve a given approximation in case a direction with insufficient descent was computed. Combined with a recently proposed deterministic gradient sampling approach, this yields a deterministic and provably convergent way to approximate subdifferentials for computing descent directions.
Keywords: Applied Mathematics; Computational Mathematics; Control and Optimization

Leibniz’s Influence on 19th Century Logic - Peckhaus, Volker (The Stanford Encyclopedia of Philosophy, first published Sep 4, 2009, substantive revision Feb 2, 2024)

Tailored second harmonic generation inTi-diffused PPLN waveguides usingmicro-heaters - Babai-Hemati, Jonas; vom Bruch, Felix; Herrmann, Harald; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics